Penggunaan Monopoli Edukatif dalam Pembelajaran Ghibah dan Tabayyun di SMPN 1 Krian - Afrida Nur Afni; Muhammad Fahmi; Ali Mas’ud (An-Nahdloh: Journal of Education and Islamic Studies, 2026)
This study aims to analyze the implementation of a modified Monopoly game as an instructional medium for teaching the concepts of ghibah and tabayyun in Islamic Religious Education at SMPN 1 Krian, as well as to examine its effects on students’ activeness and thinking speed. The game was redesigned by incorporating Islamic values, contextual case scenarios, and situations relevant to students’ daily experiences. This research employed a qualitative field study approach. Data were collected through observations, interviews, and documentation during the learning process. The findings indicate that the Monopoly-based learning activity successfully created an interactive classroom atmosphere, increased motivation, and significantly enhanced student engagement. Students became more active in discussions, expressing opinions, and making group decisions. Furthermore, the game effectively trained students’ thinking speed when responding to situations that required quick analysis based on the principles of ghibah and tabayyun. The learning experience also facilitated the gradual construction of students’ understanding through direct involvement, social interaction, and post-activity reflection. This study concludes that educational games can serve as an effective, enjoyable, and contextually relevant instructional strategy for improving students’ conceptual understanding and social skills in Islamic religious learning. Monopoly Game; Ghibah; Tabayyun; Student Activeness; Thinking Speed; Islamic Education Learning. Keywords: Monopoly Game, Ghibah, Tabayyun, Student Activeness, Thinking Speed